Wind energy : an introduction - El-Sharkawi, Mohamed A. (CRC Press, Taylor & Francis Group, 2016)
Wind energy is a substantial source of electricity. Wind power plants are installed at high capacities all over the world. With modern designs and control, wind power plants are now comparable to conventional generations in terms of capacity and control. Thus, this technology must move from the research level to the educational level. This book comprehensively covers the main aspects of wind energy types, operation, modeling, analysis, integration, and control.